1992
DOI: 10.1182/blood.v79.8.1931.bloodjournal7981931
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mechanism of anagrelide-induced thrombocytopenia in humans

Abstract: Anagrelide is a new therapeutic compound recently demonstrated to have a rapid and selective thrombocytopenic effect in humans. The effects of anagrelide were evaluated in plasma clot and liquid suspension cultures of optimally stimulated normal human peripheral blood megakaryocyte progenitors in order to determine the mechanism of its thrombocytopenic activity. In plasma clot cultures, at clinically relevant, therapeutic concentrations (5 to 50 ng/mL), anagrelide exerted no significant inhibitory effect on me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 1 publication
2
28
0
2
Order By: Relevance
“…43 EFFECT OF ANA ON MEGAKARYOPOIESIS Experimental studies were in keeping with the finding that in cell cultures ANA results in a left-shifting of megakaryocyte maturation with a decrease in ploidy. 38 These data confirm the histological evaluation of routinely (hematoxylin and eosin) stained BM slides that showed an increased number of immature megakaryocytes 39,44 consistent with a prevalence of a low-ploidy population. 45,46 However, applying flow cytometry and fluorescence-assisted cell sorting (FACs), both a decrease in cell size (modal ploidy) and also in cell mass (number of megakaryocytes) were demonstrated.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…43 EFFECT OF ANA ON MEGAKARYOPOIESIS Experimental studies were in keeping with the finding that in cell cultures ANA results in a left-shifting of megakaryocyte maturation with a decrease in ploidy. 38 These data confirm the histological evaluation of routinely (hematoxylin and eosin) stained BM slides that showed an increased number of immature megakaryocytes 39,44 consistent with a prevalence of a low-ploidy population. 45,46 However, applying flow cytometry and fluorescence-assisted cell sorting (FACs), both a decrease in cell size (modal ploidy) and also in cell mass (number of megakaryocytes) were demonstrated.…”
supporting
confidence: 81%
“…First, ANA exerts no effect on the circulating half-time of platelets, indicating that it does not enhance their premature destruction. [37][38][39] For this reason, research has focused on issues such as megakaryocyte maturation and differentiation as well as apoptosis (programmed cell death). In addition to the effects on megakaryopoiesis, recently a stimulating influence of this agent concerning the complex pathomechanisms responsible for the generation myelofibrosis [40][41][42] has been reported that caused considerable concern among clinicians.…”
mentioning
confidence: 99%
“…The effect of anagrelide on human megakaryocytopoiesis has been shown to be concentration depen dent. 48,49 In four patients with ET and one with chronic granulocytic leukemia (CGL) being treated with standard doses of anagrelide, we did not detect any change in bone marrow cellularity or the number of megakaryocytes per high-power field. 48 A similar observation was reported earlier.…”
Section: Mechanism Of Actionmentioning
confidence: 72%
“…Anagrelide hydrochloride targets the PDE3 enzyme family and reduces the peripheral blood platelet numbers by inhibiting megakaryopoiesis in the bone marrow (19,20), and is used for the treatment of essential thrombocythemia (21,22). Anagrelide inhibits the cAMP phosphodiesterase activity elevating the cAMP levels in platelets (23,24).…”
Section: Introductionmentioning
confidence: 99%